Meta-Analisis: Youtube Sebagai Media Pembelajaran Bahasa - Shiera, Aulia; Nurul Ainin Ramadhan; Mulki, Adinda Nurul Asyifa; Candra Dewi, Anita (AIJER: Algazali International Journal Of Educational Research, 2025)
Abstrac: This meta-analysis examines the use of YouTube as a language learning medium based on 15 research articles published between 2020-2024. This study aims to analyze patterns, trends, and implications of YouTube utilization in language education through document analysis of selected articles. The results show that YouTube is increasingly used in language education across different educational levels (40% in high schools, 20% each in early childhood education and higher education), with English (46.67%) and Indonesian (40%) as the most studied languages. Most research employed qualitative methods (46.67%), followed by quantitative (33.33%) and mixed methods (20%). The primary findings indicate that YouTube enhances learning effectiveness (40%), increases interest and motivation (26.67%), provides accessibility and learning flexibility (20%), enriches learning materials (20%), facilitates language acquisition in children (20%), and improves specific language skills (13.33%). The research identified several challenges including internet connectivity issues (40%), content curation needs (26.67%), limited interaction (20%), distractions (20%), and digital literacy requirements (20%). Despite these challenges, YouTube demonstrates significant positive impacts on vocabulary mastery (26.67%), concept understanding (33.33%), and learning motivation (40%). This meta-analysis provides comprehensive insights for educators and researchers regarding YouTube's effectiveness as a language learning medium.